Optimisation of the skiers trajectory in special slalom - Rudakov, R.; Lisovski, A.; Ilyalov, O.; Podgaets, R. (Procedia Engineering, 2010)
The model of alpine skier has been considered as a material particle connected with a weightless rod. The optimal ski trajectory that minimises the descent time along the special slalom track has been found with the specified values of the aerodynamic drag coefficient and the coefficient of ski-snow friction.